Sistem Informasi SPP & Pembayaran Sekolah Berbasis Web Pada Mts Al–Ihsan Pondok Gede Bekasi - Oscar, Dony; Maulana, Yana Iqbal; Haidir, Ali; Alhaq, Abdul Ghani (IJNS - Indonesian Journal on Networking and Security, 2019)
Abstract—An effective tuition payment system will trigger the performance of agencies to be better than before. Data processing the payment of spp on Mts Al-Ihsan Pondok Gede Bekasi until now are still operating manually and payment is still a presentation of data a obstacles.The problem that is often complained of is the difficulty of collecting SPP payment data which is separated in several financial books, in this case the presentation of financial statements becomes a little slow and inefficient and effective.Specifically the functions performed by the SPP & school payment information system developed include, student data collection, data collection and payment data. display payment information and display student reports, payment reports and student payment recapitulation.Information systems & payments SPP web-based school was developed with the PHP Framework Codeigniter 3, which is able to improve computer facilities in the mts al-ihsan pondok gede.With this computerized SPP payment system, it is expected to improve the data processing of SPP payments effectively and efficiently. Kata Kunci— Infomration System, School Payment, Waterfall